THE LINK BETWEEN VITAMIN В12 DEFICIENCY, RISK OF CARDIOVASCULAR DISEASES AND AGING PROCESS - O. M. Drapkina; R. N. Shepel (Столичная издательская компания, 2017)
Disorder of formation of vitamin B12, which has a wide range  of biological properties and is involved in the regulation of many important physiological functions, is the basis of a number of serious diseases. Usually internists consider that vitamin В12 deficiency is associated with disturbances of hematopoiesis or central nervous system. However cobalamin deficiency also affects the state of the cardiovascular system. Its connections to the increased incidence of myocardial infarction, stroke, and congestive heart failure were found, as well as the elevated risk of restenosis after coronary artery bypass surgery. Besides, there are data that demonstrate an association between vitamin В12 and telomere length (a marker of aging). This review presents the main reasons of cobalamin deficiency in the elderly, as well as an analysis of clinical studies that show the link between vitamin В12 deficiency and the risk of cardio-vascular diseases and aging process.